Comparison of the detrimental features of microglia and infiltrated macrophages in traumatic brain injury: A study using a hypnotic bromovalerylurea. Issue 10 (8th September 2018) - Abe, Naoki; Choudhury, Mohammed E.; Watanabe, Minori; Kawasaki, Shun; Nishihara, Tasuku; Yano, Hajime; Matsumoto, Shirabe; Kunieda, Takehiro; Kumon, Yoshiaki; Yorozuya, Toshihiro; Tanaka, Junya
Abstract: Microglia and blood‐borne macrophages in injured or diseased brains are difficult to distinguish because they share many common characteristics. However, the identification of microglia‐specific markers and the use of flow cytometry have recently made it easy to discriminate these types of cells. In this study, we analyzed the features of blood‐borne macrophages, and activated and resting microglia in a rat traumatic brain injury (TBI) model. Oxidative injury was indicated in macrophages and neurons in TBI lesions by the presence of 8‐hydroxy‐2'‐deoxyguanosine (8‐OHdG). Generation of mitochondrial reactive oxygen species (ROS) was markedly observed in granulocytes and macrophages, but not in activated or resting microglia. Dihydroethidium staining supported microglia not being the major source of ROS in TBI lesions. Furthermore, macrophages expressed NADPH oxidase 2, interleukin‐1β (IL‐1β), and CD68 at higher levels than microglia. In contrast, microglia expressed transforming growth factor β1 (TGFβ1), interleukin‐6 (IL‐6), and tumor necrosis factor α at higher levels than macrophages. A hypnotic, bromovalerylurea (BU), which has anti‐inflammatory effects, reduced both glycolysis and mitochondrial oxygen consumption. BU administration inhibited chemokine CCL2 expression, accumulation of monocytes/macrophages, 8‐OHdG generation, mitochondrial ROS generation, and proinflammatory cytokine expression, and markedly ameliorated the outcome of the TBI model. Yet, BU did not inhibit microglial activation or expression of TGFβ1 and insulin‐like growth factor 1 (IGF‐1). These results indicate that macrophages are the major aggravating cell type in TBI lesions, in particular during the acute phase. Activated microglia may even play favorable roles. Reduction of cellular energy metabolism in macrophages and suppression of CCL2 expression in injured tissue may lead to amelioration of TBI. Main Points: Infiltrated macrophages express/generate more IL‐1β and reactive oxygen species and less TGFβ1 than resident microglia in injured brains during the acute phase. Reduced CCL2 expression and cellular energy metabolism may ameliorate the recovery outcome.